Implementation of Quantum Teaching in Mathematics Learning to Improve Student’s Interest and Learning Outcome in Elementary School - Marisan Marisan; Aunurrahman Aunurrahman; Agung Hartoyo (Universitas Tanjungpura, 2021)
This study aims to describe the planning, implementation, evaluation and learning barriers of quantum teaching-based mathematics in developing student’s interest and learning outcome in elementary school. Data was obtained by observation, in-depth interviews, field records, document data analysis, and teaching and learning process documentation. Research data was checked for its validity by triangulation to obtain accurate and legitimate data. Data analysis was done through data reduction, data display, verification and conclusion. The results of the research were: (1) The quantum teaching-based mathematics lesson plan (RPP) designed by the teacher was generally qualified in the development of RPP; (2) The study of mathematics based on quantum teaching was implemented according to the program that has been drafted to foster the learning interest of learners, although sometimes it should adapt to the situation and condition that occurred suddenly; (3) The evaluation was not monotonous, evaluation of learning using several assessment instruments to make the teacher understand how to foster learning interest and ability of learners (4) Learning mathematics based on quantum teaching requires supporting means of both multi-media learning, multi learning resources and so on.